Ovitrampas para Avaliação da Presença de Aedes aegypti (Linnaeus) e Aedes albopictus (Skuse) no Município de Vassouras, Estado do Rio de Janeiro - Oliveira, Alexandre de Araujo; Maleck, Marise (EntomoBrasilis, 2014)
Aedes aegypti (Linnaeus) e Aedes albopictus (Skuse) são vetores de diversas arboviroses entre elas a febre amarela urbana e a dengue, sendo a última um dos maiores problemas no mundo em cidades que possuem clima quente e úmido. Diante dos consecutivos casos de dengue em Vassouras-RJ foi importante averiguar a presença e comportamento do vetor nas diversas épocas do ano e sua predominância no município. Neste estudo observou-se a presença de Ae. aegypti em 10,44% e Ae. albopictus em 89,56% dos 364 ovos que se tornaram viáveis, e sendo o bairro Matadouro, ponto 4, local com maior presença destes culicídeos. Estes dados mostraram que Ae. albopictus está cada vez mais presente na área urbana. Ovitraps for evaluating the presence of Aedes aegypti (Linnaeus) and Aedes albopictus (Skuse) in Vassouras City, State of Rio de Janeiro Abstract. Aedes aegypti (Linnaeus) and Aedes albopictus (Skuse) are vectors of many arboviruses including urban yellow fever and dengue, the latter being one of the biggest problems in the world in cities that have hot and humid climate. Having the consecutive cases of dengue in Vassouras, RJ it was important to ascertain the presence and behavior of the vector in different seasons of year and their predominance in the city. In this study we observed the presence of 10.44% Ae. aegypti and 89.56% Ae. albopictus of the 364 viable eggs and being the Matadouro neighborhood (point 4), the local with the largest presence of these culicids. These data showed that Ae. albopictus is ever more present in urban areas.